2020
DOI: 10.1007/s10765-020-02728-2
|View full text |Cite
|
Sign up to set email alerts
|

Density Measurements of (0.99 Methane + 0.01 Butane) and (0.98 Methane + 0.02 Isopentane) over the Temperature Range from (100 to 160) K at Pressures up to 10.8 MPa

Abstract: Densities of two methane-rich binary mixtures were measured in the homogeneous liquid and the supercritical region at temperatures between (100 and 160) K using a low-temperature single-sinker magnetic-suspension densimeter. For each mixture, four isotherms were studied over the pressure range from (0.3 to 10.8) MPa. Molar compositions of the gravimetrically prepared methane-rich binary mixtures were approximately 0.01 butane and 0.02 isopentane, respectively, with the balance being methane. The relative expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 20 publications
0
22
1
Order By: Relevance
“…As can be seen in Figure 5, the relative deviations of the experimental densities ρ exp from the interpolated reference densities ρ ref reveal that the condensation of sample into the precooled and evacuated measuring cell resulted in a slight decrease in density, which implies an enrichment of methane in the liquid phase. Nevertheless, the shift in experimental density is within the relative expanded uncertainty ( k = 2) of the experimental reference densities of less than U ( ρ )/ ρ = 0.015% 23 . We note that the uncertainty in composition of the reference gas mixture is excluded in this combined uncertainty because exactly the same mixture sample was used for the condensation experiments within the present work as for the reference measurements by Eckmann et al 23 Nevertheless, due to the consistency of the data, neither a change in composition caused by the condensation procedure nor a dependency on the filling pressure can be observed, which supports the findings of Walker et al 10 …”
Section: Assessment Of Condensation For Liquefactionmentioning
confidence: 68%
See 4 more Smart Citations
“…As can be seen in Figure 5, the relative deviations of the experimental densities ρ exp from the interpolated reference densities ρ ref reveal that the condensation of sample into the precooled and evacuated measuring cell resulted in a slight decrease in density, which implies an enrichment of methane in the liquid phase. Nevertheless, the shift in experimental density is within the relative expanded uncertainty ( k = 2) of the experimental reference densities of less than U ( ρ )/ ρ = 0.015% 23 . We note that the uncertainty in composition of the reference gas mixture is excluded in this combined uncertainty because exactly the same mixture sample was used for the condensation experiments within the present work as for the reference measurements by Eckmann et al 23 Nevertheless, due to the consistency of the data, neither a change in composition caused by the condensation procedure nor a dependency on the filling pressure can be observed, which supports the findings of Walker et al 10 …”
Section: Assessment Of Condensation For Liquefactionmentioning
confidence: 68%
“…The experimental densities were compared with reference densities of the same mixtures that were measured using a reference densimeter. 8,23 It was found that the change in composition of the liquid phase was only small when the sample was filled into the precooled and evacuated system. Here, the deviations from the reference data were within the experimental uncertainty of the reference densimeter.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations